(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is dedicated to the importance of gender equality as a legal principle aimed at ensuring equal rights and freedoms for both men and women in all areas of public life. It examines both international documents and national laws and regulations focused on protection of women’s rights and the promotion of gender equality. The article also provides relevant statistical data demonstrating positive outcomes in practice. Special attention is given to the improvement of national legislation and practical steps toward the effective implementation of gender equality.